"We always report under pressure": Professionalism and journalistic identity among regional journalists in a conflict zone. (April 2023) - Shah, Sayyed Fawad Ali; Ginossar, Tamar; Ittefaq, Muhammad
This study explores how regional journalists in Pakistan conceptualize journalistic professionalism, how they perceive their journalistic identities, and how local socio-political and economic realities shape their professional identification. Analysis of interviews with 33 journalists working in Pakistan's Pakhtunkhwa province indicated a tension between striving for professionalism as defined by Western journalistic standards and meeting the demands of their local conditions. Participants described professionalism as providing clear, accurate, objective, and ethical coverage of issues. However, constraints including unavailability of funding, the need to hold multiple jobs, threats to personal safety, and absence of education and training prevented them from meeting their professional goals. The journalists discursively negotiated and constituted their professional identities in response to the conditions in their respective areas.